(untitled) (New York, 1995)
This publication deals in depth with a limited number of culture media used in Food Science laboratories. It is basically divided into two main sections: Data on the composition, preparation, mode of use and quality control of various culture media used for the detection of food borne microbes; Reviews of several of these media, considering their selectivity and productivity and comparative performance of alternative media. Microbiologists specializing in food and related areas will find this book particularly useful.
Keywords: Food,Thực phẩm; Microbiology,Vi sinh vật